Early Childhood Education in Norway and Ukraine: A comparative overview - С. Головчук (Педагогічна освіта: теорія і практика. Психологія, педагогіка)
The improvement and global change in education are associated with cross-cultural trends and modern challenges. The comparative analysis of different systems encourages a new viewpoint on practice and educational policy. The research highlights a comparative view of Early Childhood Education (ECE) in two European countries − Norway and Ukraine, both with ancient historical and contemporary relations. This study investigates the impact of philosophical and historical aspects of both countries, as well as various state policies. The theoretical and conceptual framework is focused on the theory of child well-being by Pollard and Lee (2003). The data collection is based on the quantitative (statistics related to Early Childhood Education from both countries) and qualitative approaches (analysis and interpretation of Early Childhood Education normative documents and pedagogical literature from Norway and Ukraine). The study has been conducted per the Norwegian Guidelines for Research Ethics in the Social Sciences and the Humanities (NESH, 2021). The normative documents and pedagogical literature were interpreted with an open, independent, truthful, and critical approach, considering trust, credibility, and authenticity. The analyses, which included normative documentary interpretation and systematic literature search, were systematized into two categories: legislative framework, types of early childhood establishment, didactic approaches to Early Childhood Education in both countries. The results show that Early Childhood Education in Norway and Ukraine depends directly on the impact of national historical traditions and economic circumstances. Personal orientation and social interaction are one of the priorities in Norwegian kindergartens. Children spend a lot of time outside in all types of weather. In addition, there is a focus on collaboration and teamwo rk. In Ukrainian kindergarten, the educational process has aesthetic, ethical, physical and intellectual appro aches. The child’s intellectual development is connected to their moral growth. Moreover, positive attitudes and a good climate provide good relationships in kindergarten. In both countries, early childhood educators are open to new projects, innovations, and modern tasks, where personal interaction and the children’s mutual development are in priority